Mechanistic and Experimental Aspects of the Structural Characterization of Some Model and Real Systems by Nitrogen Sorption and Mercury Porosimetry - Carlos Felipe; Fernando Rojas; Isaac Kornhauser; Matthias Thommes; Giorgio Zgrablich (Adsorption Science & Technology)
Several mechanistic and phenomenological aspects of mercury intrusion and nitrogen sorption processes involving some model and real mesoporous systems were studied. The experimental pore systems examined consisted of two substrates: (a) a globular solid composed of monodisperse silica spheres in a perfect rhombohedral arrangement and (b) a controlled pore glass solid. Comparisons between the experimental nitrogen sorption and mercury porosimetry pore-size distributions demonstrated: (i) the existence of several mechanistic effects responsible of irreversible capillary behaviour that influences the calculation of pore structure parameters; (ii) the choice of the right sorption process (i.e. condensation or evaporation) suitable for comparison with either intrusion or extrusion results; (iii) the types of porous structures capable of convenient pore-size characterization by either nitrogen sorption and/or mercury porosimetry methods; and (iv) the nature of the pore entities (i.e. chambers or necks) that control the incumbent capillary process.